Environmental Conservation or the Treadmill of Law: a Case Study of the Post-2014 Husbandry Waste Regulations in China - Mao, KuoRay (International journal of offender therapy and comparative criminology, 2022)
As industrialized animal agriculture expanded rapidly in the last decade, the resultant pollution has generated widespread despoliation of natural resources and environmental victimization in rural China. This study examines the formulation and implementation of national environmental regulations from 2014 to 2019 and finds that the juxtaposing ministerial and provincial jurisdictions resulted in conflicting interpretations of the scale and evaluation criteria of the national policy. We argue that the regulations are more than centralized conservation programs designed to reduce environmental pollution caused by the expansion of animal husbandry. Instead, these regulations are fundamentally state-led rural development initiatives that utilize the designations of ecological protection zones to reconfigure land use and promote scale-up production in agricultural structural adjustment initiatives. The enforcement of these environmental regulations, therefore, constitutes a treadmill of law (ToL) that accelerated the geographical specialization and function intensification of the Chinese husbandry sector.